2018
DOI: 10.3390/math6110225
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Plants: Multisensory Visual-Tactile Interaction Enhances Emotional Experience

Abstract: Using a multisensory interface system, we examined how people’s emotional experiences change as their tactile sense (touching a plant) was augmented with visual sense (“seeing” their touch). Our system (the Interactive Plant system) senses the electrical capacitance of the human body and visualizes users’ tactile information on a flat screen (when the touch is gentle, the program draws small and thin roots around the pot; when the touch is more harsh or abrupt, big and thick roots are displayed). We contrasted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…103 Yamauchi et al showed that, compared with simple visual or tactile interaction, tactile and visual multisensory interaction with plants effectively enhanced the arousal level. 104 Therefore, this study speculates that rural tourists either visually appreciate the natural landscape in rural physiography, have intimate contact with the natural areas and flora and fauna through tactile touch, or listen to the various natural sounds, which all trigger emotional arousal. Moreover, the more positive the evaluation of rural physiography experienced through viewing, touching and listening, the stronger the positive arousal will be.…”
Section: Physiography and Positive Arousalmentioning
confidence: 89%
See 1 more Smart Citation
“…103 Yamauchi et al showed that, compared with simple visual or tactile interaction, tactile and visual multisensory interaction with plants effectively enhanced the arousal level. 104 Therefore, this study speculates that rural tourists either visually appreciate the natural landscape in rural physiography, have intimate contact with the natural areas and flora and fauna through tactile touch, or listen to the various natural sounds, which all trigger emotional arousal. Moreover, the more positive the evaluation of rural physiography experienced through viewing, touching and listening, the stronger the positive arousal will be.…”
Section: Physiography and Positive Arousalmentioning
confidence: 89%
“…48 Previous studies have examined the effects of physiography on arousal from the perspective of auditory, visual and tactile sensations. [101][102][103][104] As an important element of nature tourism destinations, the natural soundscape has been widely recognized as an important perceived element and ideal experience for tourists in nature tourism destinations. 101 Jiang studied the connection between the sound landscape in the natural landscape and the emotions of tourists from the perspective of the auditory senses, which shows that the natural soundscape significantly affects the emotional arousal of tourists.…”
Section: Physiography and Positive Arousalmentioning
confidence: 99%
“…Yamauchi et al further demonstrated that people's emotional experiences change as their tactile sense (touching a plant) was augmented with visual sense ("seeing" their touch) in a multisensory interface system [16]. Chen et al (2012) tried to identify possible correlations between increasing levels of cognitive demand and modalities from speech, digital pen, and freehand gesture to eye activity, galvanic skin response, and EEG [17].…”
Section: Related Workmentioning
confidence: 99%
“…Yamauchi et al combined behavioral measures and multiple mouse motion features to better predict people's emotions and cognitive conflict in computer tasks [12,13]. Yamauchi et al further demonstrated that people's emotional experiences change as their tactile sense (touching a plant) was augmented with visual sense ("seeing" their touch) in a multisensory interface system [14]. Chen et al (2012) tried to identify possible correlations between increasing levels of cognitive demand and modalities from speech, digital pen, and freehand gesture to eye activity, galvanic skin response, and EEG [15].…”
Section: Related Workmentioning
confidence: 99%